Migrant workers' perception and awareness of health insurance coverage in Brunei Darussalam - Alice Lai; Noorfaizah Mohammad; Ashish Trivedi; Zaidah Murang; Nik Tuah (BMC, 2024)
Abstract Background Migrant workers are recognized as a vulnerable group of population in the context of accessibility to healthcare services as they are likely to experience multiple challenges and barriers. This study aimed to assess the awareness and perceived knowledge on health insurance coverage among documented migrant workers in Brunei Darussalam. Methods This cross-sectional, interviewer-administered study used a pre-designed questionnaire on migrant workers attending the Foreign Worker Health Screening Centre from June until September 2019. Data were analyzed for association between perceived insurance status on health-seeking behavior. Results The study obtained responses from 469 documented migrant workers (93.8%). 75.1% reported being aware of and having health insurance coverage; and of these, 57.1% were aware of the type of health insurance cover they had. 45.5% and 50.6% had poor knowledge whether their health insurance covered for hospitalization or outpatient expenses, respectively. No significant association was found between the migrant workers' perceived status of insurance and not seeking medical care due to financial barriers (p > 0.05). Conclusions A high proportion of documented migrant workers in Brunei Darussalam reported knowledge of having health insurance; however, there was lack of awareness on its actual coverage. By including migrants' health in a nation's healthcare governance, the health rights of migrant workers can be addressed thus aiming to achieve universal health coverage for all individuals.